From nanoparticles to nanofilms: exploring effects of Zn addition for nanostructure modification and photoluminescence intensification of MoO3−x nanomaterials. (17th December 2019) - Wang, B B; Zhong, X X; Shao, R W; Chen, Y A; Cvelbar, U; Ostrikov, K
Abstract: Exploring the fast synthesis of Zn-doped MoO3− x nanostructures in a N2 environment by the hot filament chemical vapour deposition using a mixture of Zn and MoO3 powders is reported, whereas targeted transformation of nanomaterials is done via Zn addition in MoO3 powder. During this process, MoO3− x nanostructures convert from nanoparticles to nanofilms. The structural conversion of MoO3− x nanostructures is the results of the predominant diffusion of MoO3− x and MoO3 molecules along the substrate surface caused by reduced evaporation of MoO3 due to the melting of Zn particles. At room temperature, the pure and Zn-doped MoO3− x nanostructures generate the photoluminescence (PL) emission in the ultraviolet to infrared range, while the PL emission in the visible range has a great change at low temperature. The PL emission is related to the bandgap transition, Mo 5+ d – d transition, intervalence charge transfer transition, and transition between the intermediate and valence bands. Furthermore, the PL emission of MoO3− x nanostructures is enhanced by Zn doping. The strong PL emission from Zn-doped MoO3− x nanostructures compared to pure MoO3− x nanostructures results from the increase of oxygen vacancies caused by the Zn incorporation. The enhancement of PL emission at low temperature compared to room temperature is due to the increase of vacancy concentration, weak lattice vibration and relaxation of polarons. Our present results could be used to control the structures of MoO3− x nanomaterials and impact the development of optoelectronic devices based on MoO3 nanomaterials, such as organic solar cells, photovolatic devices and light-emitting diodes.